Lessons on the Constitution. Supplements to High School Courses in American History, Government and Civics - Patrick, John J.; Remy, Richard C.; American Historical Association, Washington, DC.; Social Science Education Consortium, Inc., Boulder, CO.; American Political Science Association, Washington, DC. (Washington : Distributed by ERIC Clearinghouse, 1985)
These curriculum materials about various aspects of the United States Constitution are designed as supplements to high school courses in history, civics, and government. They include 60 original lessons for students, accompanied by lesson plans for teachers, and are divided into five chapters. Chapter I, "Documents of Freedom" includes the Constitution, amendments to the Constitution, amendments proposed but not ratified, and selected Federalist papers. Chapter II, "Origins and Purposes of the Constitution" covers the concept of a constitution, state constitutions, the Articles of Confederation, the Constitutional Convention, federalists and anti-federalists, the Bill of Rights, and the timetable of main events in the making of the Constitution. Chapter III, "Principles of Government in the Constitution," deals with the concept and operation of federalism, separation of powers, the judiciary, and civil liberties. Chapter IV, "Amending and Interpreting the Constitution," deals with amendments, constitutional conventions, political parties, and challenges to the Constitution. Chapter V, "Landmark Cases of the Supreme Court," analyzes 20 crucial Supreme Court cases. (IS)
Teachers.
Practitioners.
Microfiche.
Keywords: Case Studies; Citizenship Education; Constitutional History; History Instruction; Instructional Materials; Learning Activities; Lesson Plans; Political Science; Secondary Education; Social Studies; United States History; Units of Study; Federalism -- Law Related Education -- Supreme Court; Guides, Classroom -- Teacher